Analysis of Customer Loyalty Access by KAI (Study on Access by KAI Customers in Surabaya City) - Aditya Chandra Winata; Ety Dwi Susanti (Lavish Opulent Education, 2025)
This study is motivated by the increasing use of digital services in the public transportation sector, particularly through the Access by KAI application, which facilitates practical train ticket booking for users. Customer loyalty toward this application is influenced not only by technical aspects but also by user experience and perceptions of service quality. The aim of this research is to analyze the factors that shape customer loyalty toward the Access by KAI application in the city of Surabaya. This study employs a qualitative approach, using in-depth interviews as the primary method of data collection. Informants include active users of the application as well as representatives from PT KAI DAOP 8 Surabaya Passenger Transport Unit. Interviews were conducted directly within the user environment and at Surabaya Gubeng Station to gather rich and empirical data. The findings reveal that customer loyalty is built through a combination of technical factors, such as ease of navigation and transaction security, and emotional factors, such as trust in the PT KAI brand and satisfaction with previous experiences. Despite facing technical issues such as limited features and occasional system errors, most users remained tolerant and continued using the application. The study concludes that customer loyalty results from an interaction between service quality, positive perceptions, and long-term user experience. The implications of this study contribute to the development of customer retention strategies within PT KAI and serve as a reference for enhancing digital transportation services to be more responsive to user needs and expectations